Aimmat al fiqh al tis'ah : yashtamil hadha al juz'i 'ala, al Imam Zayd Ibn 'Ali Zaynal 'Abidin, Imam Ja'far al Sadaiq, Abu Hanifah al Nu'man, Malik Ibn Anas, Al Layth Ibn Sa'd, Imam al Safi'iy - Abdurrahman al Sharqawi (Al Hay'ah al Masriyyah, 1987)
ws.jl.1-2.c.1-4